Imatinib and its combination with 2,5-dimethyl-celecoxibinduces apoptosis of human HT-29 colorectal cancer cells - Somayeh Atari-Hajipirloo; Saba Nikanfar; Amir Heydari; Fatemeh Kheradmand (Wolters Kluwer Medknow Publications, 2017)
Mono-targeting by imatinib as a main antitumor agent does not always accomplish complete cancer suppression. 2,5-dimethyl-celecoxib (DMC) is a close structural analog of the selective cyclooxygenase-2 (COX-2) inhibitor, celecoxib, that lacks COX-2 inhibitory function. In this study, we aimed to show the apoptotic effects of imatinib in combination with DMC in human HT-29 colorectal cancer (CRC) cells. HT-29 CRC cells were treated with IC 50 dose of imatinib (6.60 μM), DMC (23.45 μM), and their combination (half dose of IC 50 ) for 24 h. The caspase-3 activity was estimated with colorimetric kit. The caspase-3 gene expression was evaluated by real-time PCR method. There was a significant up-regulation in caspase-3 enzyme activity and caspase-3 expression by imatinib and its half dose combination with DMC as compared to control. As a summary, the results of this study strongly suggest that half dose combination of imatinib with DMC induced apoptosis as potent as full dose imatinib in human HT-29 CRC cells, while minimizing undesired side effects related to imatinib mono-therapy. This study also pointed towards possible caspase-dependent actions of imatinib and DMC.